AB0970 LONG-TERM FOLLOW-UP OF PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS IN A MEXICAN CENTER. (June 2019) - Fortuna, Brenda; Ochoa-Alderete, Lucero; Guerra, Fernando; García-Rodriguez, Fernando; Torres, Daniela; Villarreal-Trevino, Ana; De la O-Cavazos, Manuel E.; Rubio, Nadina
Abstract : Background: JIA comprises an heterogeneous group of diseases characterized by chronic arthritis, of unknown etiology, and onset age before 16. (1) Juvenile Idiopathic Arthritis(1) is the most common chronic rheumatic disease in children, being an important cause of disability, affecting quality of life (2). There are several subtypes of the disease, despite oligoarticular course has been described as the most frequently seen, up to 50% of JIA cases presented a polyarticular disease (4 3). Data suggest that patients who receive early therapeutic intervention are more likely to reach clinical remission. In a systematic review, Wallace's criteria were used to determine drug remission and inactive disease. They reported 7% and 47% of patients reached remission at 1.5 and 10 years, respectively. Oligoarticular patients had a shorter time to remission, while polyarticular positive rheumatoid factor were the least likely to achieve it (5). Mexico belongs to a group of developing countries where there is limited information about incidence, prevalence, clinical features, age and time to diagnosis, treatment, and remission of JIA patients. Objectives: The aim of the study is to describe demographics, clinical data and long-term follow-up of a cohort of juvenile idiopathic arthritis patients in a Mexican center. Methods: The study design was observational with no intervention, ambispective, among patients with JIA, according to ILAR criteria of pediatric rheumatology clinic from University Hospital "Dr. José Eleuterio González" over a 2-year period (2016-2018). Medical records of patients were retrospectively reviewed and collected information as demographics, age at diagnosis, disease activity, joints involved, treatment, adverse events, clinical inactivity and remission. Statistical analysis was descriptive with measure of central tendency. For continuous variables, mean, median, interquartile range and standard deviation were used to present data. Results: We enrolled 70 patients with JIA, 52 (74%) female, with a median age at diagnosis of 11.7 years. The most frequent subtype was polyarticular positive rheumatoid factor (25, 36%). Eighty adverse events were reported; 45 of special interest. The median time to remission observed was 61 months (95% CI 43.3-78.6); 33 (47%) patients reached inactive disease (Figure 1 ). Conclusion: The rates of adverse events was low, demonstrating a good safety profile of the treatment, however time to remission is greater than reported in literature. References: [1] Ravelli A, Martini A. Juvenile idiopathic arthritis. Lancet. 2007;369(9563):767–78. [2] Ruperto N, Ravelli A, Levinson JE, Shear ES, Murray K, Link Tague B, et al. Long-term health outcomes and quality of life in American and Italian inception cohorts of patients with juvenile rheumatoid arthritis. II. Early predictors of outcome. J Rheumatol [Internet]. 1997;24(5):952–8. Available from: http://www.ncbi.nlm.nih.gov/entrez/query.fcgi?cmd=Retrieve&db=PubMed&dopt=Citation&list_uids=9150088 [3] Thierry S, Fautrel B, Lemelle I, Guillemin F. Prevalence and incidence of juvenile idiopathic arthritis: A systematic review. Vol. 81, Joint Bone Spine. 2014. p. 112–7. [4] Minden K, Horneff G, Niewerth M, Seipelt E, Aringer M, Aries P, et al. The time of DMARD start in Juvenile Idiopathic Arthritis determines the likelihood of a drug-free remission in young adulthood. Arthritis Care Res (Hoboken) [Internet]. 2018; Available from: [5] Shoop-Worrall SJW, Kearsley-Fleet L, Thomson W, Verstappen SMM, Hyrich KL. How common is remission in juvenile idiopathic arthritis: A systematic review. Vol. 47, Seminars in Arthritis and Rheumatism. 2017. p. 331–7. Disclosure of Interests: None declared